Ibn Agroom's Kufic tendencies in the body of Al-Ajromiya - Muhammad, Muhammad Saad (Al-Adab Journal, 2015)
The present study intends to explore views and perspectives of the Arab grammarian Ibn-ajroom Al-sanhaaji throughout his book "An introduction to Ajroomism ". More specifically, this study tries to examine Ibn-ajroom tendency to adopt the approach of Alkufa doctrine of Arabic language grammar in two ways : parsing or sentence structure analysis and grammatical terminologies . What actually lead me to consider this issue is several attempts that made by a lot of Arab grammarians in order to regard Ibn –Ajroom as one of those grammarians who belong to Alkufa school of the Arabic grammar in spite of the fact that he was a latecomer grammarian and most of his contemporaries or generation belong to the elective approach of syntactic and grammatical analysis which are Baghdadi, Andalusia and Egyptian schools of grammar . This of course, raised a very important question into my mind that is : how can we consider Ibn –ajromm as a keen follower to Alkfua doctrine of grammar though he came historically after the presence of this school of grammar . As it will be shown throughout this study , this Arab scholar has revealed great tendency towards adopting grammatical viewpoints that mainly introduced by Alkufa school of grammar however, some of his own findings ,views and perspectives in this regard have been found to be consistent and in line and conformity with those of Albisraha school of Arabic grammar. In the first part of this study the earliest emergence of the Arabic language grammar and its origins will be thoroughly reviewed followed by a brief account of the two major schools of Arabic language grammar : Albisrha and Alkufa and then a comprehensive and full biography of Ibn-ajroom will be given before to highlight and discuss his own views , insights and perceptions regarding grammatical structure and sentence parsing and explain how they are much interrelated and consistent with Alkufa school of Arabic language grammar